World orders, old and new - Chomsky, Noam
In this widely acclaimed study of global politics, Chomsky offers a devastating critique of conventional definitions of the 'new world order'. It is, he argues, nothing more than an ingenious piece of 'historical engineering', whereby the pretexts for the Cold War - nuclear threat, Eastern Bloc menace - have been deftly replaced by a new set of convenient justifications for a Western agenda that remains largely unchanged.